2021
DOI: 10.1049/ell2.12298
|View full text |Cite
|
Sign up to set email alerts
|

>25 W pulses from 1.5 μm double‐asymmetric waveguide, 100 μm stripe laser diode with bulk active layer

Abstract: The experimental characterization of a high-power pulsed semiconductor laser operating in the eye-safe spectral range (wavelength around 1.5 µm), with an asymmetric waveguide structure, a 100 µm wide stripe, and a bulk active layer positioned very close to the p-cladding, is reported. An anti-reflection/high reflection coated laser with a stripe width of 100 µm exhibits a single-facet output power over 25 W at a pumping current amplitude of 100 A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Recent experimental results confirm the advantages of this structure in minimising the internal loss effect and achieving high pulsed powers at the long wavelength (∼1.5 µm) [5,6].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recent experimental results confirm the advantages of this structure in minimising the internal loss effect and achieving high pulsed powers at the long wavelength (∼1.5 µm) [5,6].…”
Section: Introductionmentioning
confidence: 54%
“…As is well known, highly efficient operation of a semiconductor laser requires, firstly, low parasitic losses (both built-in and injection-dependent) and, secondly, high injection efficiency (which in turn requires low electron current leakage into the p-cladding). As discussed in the Introduction, it has been already shown that the first of these effects is effectively suppressed (at any wavelength) in the double-asymmetric structure of the type shown here, with both bulk and QW AL [1][2][3][4][5][6][13][14][15][16]. Therefore we shall concentrate on the second of the two considerations, the current leakage, which is known to be a significant threat in visible-range emitting lasers (see e.g.…”
Section: Analysis Of Laser Efficiencymentioning
confidence: 74%
“…In the previous papers (see [1,2,3] and references therein), we proposed and analysed a high-power semiconductor laser design using an asymmetric large optical cavity waveguide (with different refractive index steps at the interfaces between the Optical Confinement Layer (OCL) and the nand p-claddings, and a relatively thick (typically bulk) active layer (AL) positioned very near the p-cladding. The design was shown to offer a number of advantages for lasers operating in a pulsed regime at wavelengths from visible (red) [3] through near infrared (800-900 nm [2]) to the eye safe wavelengths (~1.5 m [1], as confirmed by the recent experimental results [4,5]). Specifically for red lasers, an important advantage of this design, in addition to single transverse mode operation with a relatively narrow far field, included a suppressed current leakage and hence improved injection efficiency at high pulse power.…”
mentioning
confidence: 75%
“…As in [3], the waveguide used is a large optical cavity (LOC) strongly asymmetric one, with the refractive index step at the interface between the OCL and the n-cladding substantially smaller than that at the OCL/p-cladding interface. The bulk (GaInP) AL is positioned at a very short distance (50 nm) from the pcladding (note that the location of the active layer, bulk or Quantum Well, near the p-cladding is currently widely accepted for high-power semiconductor lasers [4,5,8,9,10,11]). As noted previously [1][2][3], in a waveguide of this type, unlike in most structures with Quantum Well based active layers, the AL itself contributes noticeably to the waveguiding properties of the structure, strongly affecting the shape of the mode.…”
mentioning
confidence: 99%